Amniotic epithelial cells promote wound healing in mice through high epithelialization and engraftment. (15th July 2015) - Jin, Enze; Kim, Tae‐Hee; Han, Seongho; Kim, Sung‐Whan
Abstract: Although human amniotic epithelial cells (AMEs) are an attractive source of stem cells, their therapeutic potential in wound healing has not been fully investigated. We evaluated the therapeutic potential of AMEs for wound healing. Real‐time PCR showed that the epithelialization growth factors epidermal growth factor (EGF), platelet‐derived growth factor (PDGF)‐B and chemotactic factors interleukin‐8 (IL‐8 or CXCL8) and neutrophil‐activating protein‐2 (NAP‐2 or CXCL7) were upregulated in AMEs compared with adipose‐derived mesenchymal stem cells (ADMs). In vitro scratch wound assays revealed that AME‐derived conditioned medium substantially accelerated wound closure. Wounds in NOD/SCID mice were created by skin excision, followed by AME transplantation. AMEs implantation significantly accelerated wound healing and increased cellularity and re‐epithelialization. Transplanted AMEs exhibited high engraftment rates and expressed keratinocyte‐specific proteins and cytokeratin in the wound area, suggesting direct benefits for cutaneous closure. Taken together, these data indicate that AMEs possess therapeutic capability for wound healing through the secretion of epithelialization growth factors and enhanced engraftment properties. Copyright © 2015 John Wiley & Sons, Ltd.